Evaluation of different casing material for cultivation of milky mushroom - Vijaykumar, Gitte; John, Priya; Ganesh, Kotgire (Mushroom Research, 2015)
Milky mushroom (Calocybe indica) has a wide scope under south Gujarat conditions. The experiments were conducted to find out superior casing material for cultivation of milky mushroom. Among the six different casing materials tested soil + sand was proved to be the best casing material in both paddy as well as wheat straw based substrate.Â Wheat straw as a substrate with soil + sand as casing material recorded minimum days for spawn run (15.67 days), pinhead formation (28.67 days) and first harvest (33.67 days) with highest no. of fruit bodies (24.33), diameter of pileus (7.66 cm), length of stalk (7.86 cm) and biological efficiency (146.3 per cent).